Trabectedin in the Neoadjuvant Treatment of High-Grade Pleomorphic Sarcoma: Report of a Rare Case and Literature Review - Markus K. Schuler; Stephan Richter; Ivan Platzek; Bettina Beuthien-Baumann; Kathrin Wieczorek; Christine Hamann; Johannes Mohm; Gerhard Ehninger (Case Reports in Oncological Medicine)
Background. Pleomorphic sarcoma is an aggressive soft tissue sarcoma. In patients with high-risk extremity sarcomas, the significant survival benefits conferred by an intense regimen of neoadjuvant chemoradiotherapy and surgery were reported. To our knowledge, this is the first report in the literature of the neoadjuvant use of trabectedin in a patient with high-grade pleomorphic sarcoma, ineligible for standard neoadjuvant combination therapy with an anthracycline-based regimen. Case Presentation. Here we present a 58-year-old White male with a large tumor in the left thigh, but with no signs of metastases. Owing to the history of severe heart attack, three cycles of neoadjuvant trabectedin were administrated to achieve surgically wide margins. After two cycles, an 18F-FDG-PET showed a large proportion of the central tumor area was without metabolic activity. According to RECIST and Choi criteria, the tumor was stable. After the third cycle of trabectedin, the patient underwent a complete resection, which revealed completely necrotic high-grade pleomorphic sarcoma (stage pT2b), with only a small vital area. Conclusion. The present paper on a promising treatment with neoadjuvant trabectedin of patients with high-grade pleomorphic sarcoma might suggest that such treatment approach may provide a greater chance of cure and survival of such patients.